Роль міжнародних організацій у процесі становлення та розвитку багатомовної освіти в країнах Європи - Першукова, Оксана (Studies in Comparative Education, 2014)
Статтю присвячено ретроспективному аналізу документів міжнародних організацій (ООН, ЮНЕСКО, ОБСЄ, Рада Європи, Європейський Союз), в яких намічено орієнтири для національних політик для збереження і розвитку багатомовності. Особливу увагу присвячено вивченню діяльності і визначенню стратегії діяльності цих інституцій в аспекті розвитку багатомовної освіти школярів у країнах Європи. Автором визначено загальні напрямки діяльності міжнародних організацій у розвитку цього педагогічного явища та окремо окреслено роль кожної з них. Статья посвящена ретроспективному анализу документов международных организаций (ООН, ЮНЕСКО, ОБСЕ, Совет Европы, Европейский Союз), в которых намечены ориентиры для национальных политик по сохранению и развитию многоязычия. Особое внимание уделено изучению деятельности и определению стратегии этих институтов в аспекте развития многоязычного образования школьников в странах Европы. Автором определены общие направления деятельности международных организаций и отдельно обозначена роль каждой из организаций в развитии этого педагогического феномена. The article deals with the retrospective analysis of the documents of international organizations: United Nations Organization (UN), it’s special agency the United Nations Educational Scientific and Cultural Organization (UNESCO), Organization for Security and Cooperation in Europe (OSCE), Council of Europe (CE) and European Union (EU) in which guidelines for national politics on preserving and developing multilingualism are provided. Special attention is paid to these institutions’ activity learning and strategy defining in the aspect of multilingual education of schoolchildren development in European countries. The author substantiated basic directions of international organizations activities. They are designed to create a rational and constructive plan of conservation and development of multilingual population in coordination with the ideology of peace and brotherhood. This plan is designed for long-term implementation and accompanied by constant analysis and monitoring. Following the ideology of peace and cooperation activities of international organizations in the field of language education is focused on a combination of global, national and regional trends in the society, taking into account socio-economic, political and cultural contexts of different countries, and are as follows: 1) analysis and synthesis of experience on multilingualism preserving and development including due to school multilingual education; 2) definition of common problems of modern education and finding the ways of its development including the formation of plurilingualism; 3) peer review at various levels: from country’s language policy to the level of language proficiency definition of separately taken personality; 4) implementation and coordination of regulatory work. This activity also provides benchmarks for national educational policies and common to all countries proposals, which are subject specifications at national, regional and local levels. The aim of this process is to put the idea of a society of equal opportunities into reality. Special attention is also paid to the specific role of every organization in the development this educational phenomena identification.